2022
DOI: 10.3390/foods11244108
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Correlation of Rosa roxburghii Tratt Fruit Vinegar on Obesity, Dyslipidemia and Intestinal Microbiota Disorder in High-Fat Diet Mice

Abstract: To investigate the effect of Rosa roxburghii Tratt fruit vinegar (RFV) on the intervention of obesity and hyperlipidemia and its potential mechanism, a high-fat diet (HFD)-induced obesity model in mice was established and gavaged with RFV, saline and xuezhikang for 30 consecutive days, respectively. The results showed that RFV supplementation significantly reduced fat accumulation, and improved dyslipidemia and liver inflammation in HFD mice. RFV intervention for 30 days significantly improved the diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…When compared to the NC group, the intestinal tracts of the mice given a high-fat diet had fewer Lachnospiraceae and more Desulfovibrionaceae and Prevotellaceae, which is consistent with studies in the literature [17,34]. Lachnospiraceae are involved in carbohydrate metabolism, fermenting acetic and butyric acids to provide energy for the host [36,37]. Inflammatory disorders had a positive correlation with prevotellaceae [38], and Desulfovibrionaceae belongs to the genus of harmful intestinal Bacteria, which was positively associated with the indicators of hyperlipidemia in the body [39].…”
Section: Discussionsupporting
confidence: 87%
“…When compared to the NC group, the intestinal tracts of the mice given a high-fat diet had fewer Lachnospiraceae and more Desulfovibrionaceae and Prevotellaceae, which is consistent with studies in the literature [17,34]. Lachnospiraceae are involved in carbohydrate metabolism, fermenting acetic and butyric acids to provide energy for the host [36,37]. Inflammatory disorders had a positive correlation with prevotellaceae [38], and Desulfovibrionaceae belongs to the genus of harmful intestinal Bacteria, which was positively associated with the indicators of hyperlipidemia in the body [39].…”
Section: Discussionsupporting
confidence: 87%
“…Peptostreptococcaceae plays a role in atherosclerosis (60). The relative abundance of Ruminococcaceae decreased in the vinegar group, consistent with Li et al (61). Akkermansia is a Gram-negative bacterium belonging to the Verrucomicrobacteria, which produces mucin-degrading enzymes that ferment mucin to acetate, propionate and sulfate (62), according to clinical and preclinical studies, Akkermansia was found to be negatively associated with metabolic disorders (63)(64)(65).…”
Section: Discussionsupporting
confidence: 58%
“…It is in negative correlation with BMI, waist circumference, TG and other factors related to obesity or signs of metabolic disorder. 30 As shown in Fig. 4(h), the Desulfobacterota in the model group was significantly reduced compared with the control group, but COST could significantly improve the Desulfobacterota content and reverse the structural changes of the gut microbiota induced by HFD.…”
Section: Papermentioning
confidence: 82%